2016
DOI: 10.1111/jth.13257
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid antibodies and the risk of severe and non‐severe pre‐eclampsia: the NOHA case‐control study

Abstract: To cite this article: Marchetti T, de Moerloose P, Gris JC. Antiphospholipid antibodies and the risk of severe and non-severe pre-eclampsia:the NOHA case-control study. J Thromb Haemost 2016; 14: 675-84. EssentialsWe studied the incidence of antiphospholipid antibodies (aPLs) in women with previous pre-eclampsia. Plasma was tested for classical aPLs and other 'new' antibodies such as antib2GP1 domain I IgG. Severe pre-eclampsia is distinct from non-severe and is mainly associated with antib2GP1 IgG. Specific a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Anti‐PS/PT antibodies are another major type of aPL responsible for LAC activity, in addition to anti‐β 2 GPI antibodies . They are frequently detected in patients with APS and are strongly correlated with the occurrence of thrombosis and obstetric complications .…”
Section: Introductionmentioning
confidence: 99%
“…Anti‐PS/PT antibodies are another major type of aPL responsible for LAC activity, in addition to anti‐β 2 GPI antibodies . They are frequently detected in patients with APS and are strongly correlated with the occurrence of thrombosis and obstetric complications .…”
Section: Introductionmentioning
confidence: 99%
“…In a nested case-control study evaluating 342 cases with preeclampsia compared with 195 controls without preeclampsia, anti-β2GP1 (> 99th percentile) was associated with preeclampsia in severe cases but not in mild (nonsevere) cases. 2 Similarly, only an association between anti-β2GP1 and severe preeclampsia was found in a Spanish case-control study of 182 patients. 22 In contrast, another case-control study found no association with anti-β2GP1 antibodies in women with any form of preeclampsia, including those with HELLP (Hemolysis, Elevated Liver enzyme levels, and Low Platelet levels), severe or early-onset (< 34 weeks' gestation) preeclampsia, when compared with women without preeclampsia.…”
Section: Discussionmentioning
confidence: 95%
“…Unfortunately, the link between anti-β2GP1 antibody positivity and obstetrical complications is tenuous. [1][2][3][4] If we can confirm an association between anti-β2GP1 antibody positivity and placentamediated pregnancy complications, then we can strengthen screening recommendations and advance research aimed at modifying this risk. 5 Placenta-mediated pregnancy complications include preeclampsia, placental abruption, late pregnancy loss, and birth of a small-for-gestational age (SGA) infant; the etiology is often multifactorial and may include abnormal coagulation activation at the maternal-fetal interface.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15 Marchetti et al reported no association between Anti β2 GPI IgG and non-severe pre-eclampsia, but reported a significant association in cases of severe pre-eclampsia. 16 Rezk et al stated that there was no significant relation between Anti β2 GPI and development of pre-eclampsia, but its presence is an independent risk factor of pregnancy loss. 17 Anti-cardiolipin antibodies were negative in 100% of cases of both high risk and control groups with no significant difference in mean levels between both study groups nor between the three subgroups and the control groups except for the mean level of Anti-cardiolipin IgG antibodies among high risk group which was significantly lower than that of the control group suggesting higher but still normal level in the control group.…”
mentioning
confidence: 99%